(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Mustard is a leading oil crop in Bangladesh. Relevant data and information on the adoption of improved mustard varieties is very scanty and sporadic in Bangladesh. Therefore, an attempt was made to assess the extent of adoption of improved mustard varieties and their management practices at farm level. The study used data from 540 mustard growing farmers under Manikgonj, Rajshahi and Dinajpur districts. Probit regression model along with other descriptive statistics were used to analyze the collected data. Analysis revealed that the farm level adoption of different production practices were not encouraging as most farmers did not follow the recommendations made by Bangladesh Agricultural Research Institute (BARI) for mustard cultivation. The variety adoption scenario was also discouraging since only 40% of the farmers cultivated improved mustard varieties. However, farmers showed positive attitude towards adoption of improved mustard varieties since about 53% of the adopters wanted to increase area under improve mustard cultivation in next growing season considering the high yielding ability, low cultivation cost, high profit, and less labour requirements. Although mustard is considered to be a profitable crop, many farmers showed negative attitude towards its production due to some drawbacks. Non-availability of improved mustard seed was also found to be a barrier to its adoption at farm level. Bangladesh J. Agril. Res. 40(3): 363-379, September 2015